Bilateral transfer of motor performance as a function of motor imagery training: a systematic review and meta-analysis - Yao, Wan X.; Ge, Sha; Zhang, John Q.; Hemmat, Parisa; Jiang, Bo Y.; Liu, Xiao J.; Lu, Xing; Yaghi, Zayd; Yue, Guang H. (Frontiers in Psychology, 2023)
Objective: The current review was aimed to determine the effectiveness of mental imagery training (MIT) on inducing bilateral transfer (BT) of motor performance for healthy subjects. Data Sources: Six electronic databases were searched from July 2022 to December 2022. Search terms included: ‘‘motor imagery training’’, ‘‘motor imagery practice’’, ‘‘mental practice’’, “mental training”, ‘‘movement imagery’’, “cognitive training”, ‘‘bilateral transfer’’, ‘‘interlimb transfer’’, “cross education”, “motor learning”, “strength”, “force” and “motor performance”. Study Selection and data extraction: Randomized-controlled-trials of MIT in inducing BT were selected. The decision on whether a study met the inclusion criteria of the review was made by two reviewers independently. Any disagreements between the two reviewers were first resolved by discussion between the two reviewers. If consensus could not be reached, then it would be arbitrated by a third reviewer. Nine articles were selected from the originally identified 728 studies for the meta-analysis. Data Synthesis: The meta-analysis included 14 studies for the comparison between MIT and no-exercise control (CTR) and 15 studies for the comparison between MIT and physical training (PT). Results: MIT demonstrated significant benefit on inducing BT when compared with no exercise, Effect Size (ES)=0.78, 95% confidence interval (CI)=0.57 – 0.98, favoring MIT. In addition, the meta-analysis found that the effect of MIT on BT was comparable to that of PT, ES=-0.02, 95% CI=-0.15 – 0.17. Furthermore, subgroup analyses demonstrated that MIT was more effective for internal MIT (ES=2.17, 95% CI=1.57 – 2.76) than external MIT (ES, 0.95, 95% CI, 0.74 – 1.17) and for mixed-task (ES=1.68, 95% CI=1.26 – 2.11) than mirror-task (ES = 0.46, 95% CI = 0.14 – 0.78) and normal-task (ES=0.56, 95% CI=0.23 – 0.90). No significant difference was found between transfer from dominant limb (DH) to non-dominant limb (NDL) (ES = 0.67, 95% CI=0.37 – 0.97) and transfer from NDL to DL (ES=0.87, 95% CI=0.59 – 1.15). Conclusions: This review demonstrates that MIT has better estimated effects on inducing BT compared to no exercise, and is comparable to PT. The subgroup group analyses also indicate that IMIT and mixed task result in better BT than EMIT and mirror task and normal task.